OPPORTUNISTIC BACTERIA IN AGROECOSYSTEMS OF UKRAINE - L. M. Butsenko; L. A. Pasichnyk (International Journal of Medicine and Medical Research, 2018)
Background. Recently, the number of diseases caused by opportunistic bacteria has been increasing all over the world. Opportunistic microorganisms are characterized by ubiquitous proliferation, flexibility in adaptation to the conditions of the environment, lack of specific relationship with the macroorganism. Phytopathogenic bacteria are also able to infect both plants and animals.